KIDE School Bullying Prevention and Learning Facilitation Program (Journal of Parents and Teachers, 2018)
Since conflict is an inherent part of interpersonal relationships, fostering positive coexistence and providing adequate tools to resolve peaceful conflicts and in a dialogue with one of the basic objectives of education. In the program of coexistence KIDE (dynamics of school coexistence) includes the corner of consensus, the service of school mediation, student mediators assistants, the program of cybercriminals. In order to be valid and functional, it is essential to develop the socio-emotional competencies within the curriculum, in a systematic and sequential manner from the Early Childhood Education.
Keywords: socio-emotional competencies; conflict; mediation; dialogue; repair